(untitled) (Bangladesh Journal of Nuclear Medicine, 2017)
Imaging of urinary tract plays a very important role in children with recurrent urinary tract infection (UTI). Various imaging techniques are used and the imaging protocol in children with UTI continues to be a subject of debate. Most authors recommended combination of imaging. The children with recurrent urine infection may be at increased risk of renal parenchymal scarring, hypertension, impaired renal function and end stage renal disease. But early diagnosis and timely proper treatment has an excellent prognosis. 99m-Tc-dimercaptosuccinic acid (DMSA) renal scan and Ultrasonography (US) are routinely performed studies in children with recurrent UTI. If there is agreement between these two investigation procedures, they will be interchangeable, which will benefit the patient by one procedure instead of two. This will be less time consuming and cost effective. This analytical study was carried out at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Bangabandhu Sheikh Mujib Medical University campus, Dhaka, from July 2013 to June 2014, for a period of 12 months. The objective of this study was to assess the agreement between 99mTcdimercaptosuccinic acid (DMSA) renal scan and Ultrasonography (US) US for evaluating the renal size, renal position, pelvicalyceal dilatation, hydronephrosis and renal scarring in children with recurrent UTI. Study population consisted of 85 children with age range of 6 months to 12 years, who had laboratory evidence of at least two incidence of UTI within 6 months period. All children underwent 99mTc-DMSA renal scan (plannar) and renal tract ultrasonography (US). Among 85 children, 26 (30.6%) had normal DMSA scan and 59 (69.4%) had abnormal DMSA scan findings. In case of US, 23 (27.1%) had normal US findings and 62 (72.9%) had abnormal US findings of renal system. The comparison of DMSA renal scan and US findings were done by Kappa analysis to see their agreement in the evaluation of size, position, pelvicalyceal dilatation and hydronephrosis. This study gave an impression that DMSA scan and US has good agreement in the evaluation of renal size, position of the kidney and fair agreement in the evaluation of presence of hydronephrosis. In case of mild pelvicaliceal dilatation evaluation, DMSA was underestimated comparing to US. The overall accuracy of US for the evaluation of focal scarring of right and left kidney were 89.4% and 78.8% respectively. For the evaluation of diffuse scarring the overall accuracy of US were 92.9% and 97.6% for the right and left kidney respectively. Therefore, in the evaluation of renal scarring the accuracy of US was underestimated by using DMSA scan as a gold standard. In the evaluation of kidney size, position and presence of hydronephrosis, both DMSA and US can be interchangeable. Whereas DMSA was underestimated comparing to US in the evaluation of mild pelvicaliceal dilatation. On the other hand DMSA renal scan is more sensitive and specific for detecting cortical scaring compared to the US. In light of present study, both DMSA scan and US are recommended in the combination for complete evaluation of renal abnormalities in recurrent UTI. Bangladesh J. Nuclear Med. 18(1): 32-38, January 2015